2016
DOI: 10.2196/jmir.5474
|View full text |Cite
|
Sign up to set email alerts
|

A Technology-Mediated Behavioral Weight Gain Prevention Intervention for College Students: Controlled, Quasi-Experimental Study

Abstract: BackgroundBoth men and women are vulnerable to weight gain during the college years, and this phenomenon is linked to an increased risk of several chronic diseases and mortality. Technology represents an attractive medium for the delivery of weight control interventions focused on college students, given its reach and appeal among this population. However, few technology-mediated weight gain prevention interventions have been evaluated for college students.ObjectiveThis study examined a new technology-based, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 55 publications
(66 reference statements)
1
80
0
Order By: Relevance
“…As three studies did not report the mean change in body weight and two were not lifestyle programme based , they were excluded from the review. This left 30 studies, from 33 papers , included in the review. The PRISMA flow diagram for the review process of study selection is shown in Fig .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As three studies did not report the mean change in body weight and two were not lifestyle programme based , they were excluded from the review. This left 30 studies, from 33 papers , included in the review. The PRISMA flow diagram for the review process of study selection is shown in Fig .…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published between 1998 and 2017 (Table ). Of these 30 studies, 27 were RCTs and the remaining three were pre‐test and post‐test or quasi‐experimental studies . Twenty‐two were conducted in the United States of America (USA), four were conducted in Australia, two in Canada and one each in the United Kingdom and Sweden .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Majority of young university students use extreme amount of sugar-sweetened refreshments and less utilization of recommended amount of whole grains, natural products, vegetables, calcium and drink fresh fruit juice daily. These wrong habits cause obesity, diabetes and other health problems among students (West et al, 2016).…”
Section: Research Articlementioning
confidence: 99%